Keaslian Hadis "Sultan adalah Bayangan Allah di Bumi" dan Popularitasnya dalam Sejarah Politik Islam - Syamsudin Syamsudin; Sigit Budiyanto (AL-TAHRIR, 2025)
The authenticity and political interpretation of the ḥadīth al-sulṭān ẓillullāh fī al-arḍ remain contested within Islamic scholarship, particularly concerning its role in legitimizing monarchical authority. This study investigates the ḥadīth through isnād criticism, matn criticism, and historical contextualisation. Primary sources include Kitāb al-Sunnah by Ibn Abī ʿĀṣim, Tahdhīb al-Tahdhīb by Ibn Ḥajar al-ʿAsqalānī, Syuʿab al-Īmān by al-Bayhaqī, complemented by Kuntowijoyo’s historical methodology. The findings reveal that while some transmitters are problematic, the existence of multiple transmission chains elevates the ḥadīth to the status of ḥasan li-ghayrih. In terms of matn, its content corresponds to Qur’anic principles of justice (ʿadālah) and consultation (shūrā), framing leadership as a trust and a moral legitimacy for just rulers, rather than the sacralization of political authority. Historically, the circulation of this ḥadīth from the Umayyad and Abbasid periods to the Malay-Indonesian sultanates demonstrates its use as a political instrument to sustain authority. Theoretically, this study contributes to Islamic political thought by demonstrating that political aḥadīth function not only as normative-religious texts but also as mechanisms of legitimation and critique of power. Future research is recommended to employ comparative-historical and hermeneutical approaches to further contextualize the role of political ḥadīths in both classical Islamic governance and contemporary contexts.